Integrating agricultural innovation and inclusive value-chain development: Introduction - Devaux, André; Velasco, Claudio; Jager, Matthias (International Food Policy Research Institute, 2016)
Six chapters examine efforts to promote innovation in value chains for beef cattle, dairy, potatoes, and other commodities in Africa south of the Sahara, the Andean region of South America, the Middle East, and South-East Asia. Virtually all began as research to boost farm-level productivity. However, as the importance of marketing issues became apparent, the approaches evolved to embrace inclusive value-chain development (VCD). Three of the chapters deal with general issues of linking agricultural innovation with VCD and emphasize the importance of integrating the two approaches. The other three chapters focus on the use of multistakeholder platforms to foster innovation, value-chain coordination, and governance, highlighting the crucial roles played by facilitators in platform formation, operation, and evaluation; the tensions that need to be managed; and the dynamic nature of platforms, innovation, and VCD processes. The latter highlight the need for adaptive management and learning-oriented evaluation that supports decisionmaking.